Contribution of the Interaction of Streptococcus mutans Serotype k Strains with Fibrinogen to the Pathogenicity of Infective Endocarditis - Nomura, Ryota (Infect Immun, 2014)
Streptococcus mutans, a pathogen responsible for dental caries, is occasionally isolated from the blood of patients with bacteremia and infective endocarditis (IE). Our previous study demonstrated that serotype k-specific bacterial DNA is frequently detected in S. mutans-positive heart valve specimens extirpated from IE patients. However, the reason for this frequent detection remains unknown. In the present study, we analyzed the virulence of IE from S. mutans strains, focusing on the characterization of serotype k strains, most of which are positive for the 120-kDa cell surface collagen-binding protein Cbm and negative for the 190-kDa protein antigen (PA) known as SpaP, P1, antigen I/II, and other designations. Fibrinogen-binding assays were performed with 85 clinical strains classified by Cbm and PA expression levels. The Cbm(+)/PA(−) group strains had significantly higher fibrinogen-binding rates than the other groups. Analysis of platelet aggregation revealed that SA31, a Cbm(+)/PA(−) strain, induced an increased level of aggregation in the presence of fibrinogen, while negligible aggregation was induced by the Cbm-defective isogenic mutant SA31CBD. A rat IE model with an artificial impairment of the aortic valve created using a catheter showed that extirpated heart valves in the SA31 group displayed a prominent vegetation mass not seen in those in the SA31CBD group. These findings could explain why Cbm(+)/PA(−) strains are highly virulent and are related to the development of IE, and the findings could also explain the frequent detection of serotype k DNA in S. mutans-positive heart valve clinical specimens.